Sistem Informasi Penerimaan Siswa Baru Berbasis Web di SMP DIPO Cimanggu Cilacap - ferdian, mohammad (Jurnal Teknologi dan Bisnis, 2020)
In the era of digital media development, which is increasingly rapid, almost everyone of all ages is in dire need of digital media that is connected to the internet so that people can provide and receive information quickly. With the implementation of school closures since March 16, 2020 due to the global Covid-19 pandemic, schools are carrying out online learning activities. With these conditions, the school must have an appropriate marketing strategy, the school must be able to carry out the process of admitting new students. So that many prospective students will register at the school even though the school is still not open. The solution that can be done access the website anywhere and anytime so that they can receive information about the school quickly, precisely, and accurately and carry out the registration process as prospective students without having to come to school. The development of a new student admission information system is designed using the Waterfall Method with the stages being carried out, namely needs analysis, design, programming, testing, and support or maintenance.